Edukasi Pemanfaatan Prenatal Class dalam Mengurangi Ketidaknyamanan Selama Kehamilan di Klinik Juliana Dalimunthe Tahun 2023 - Yetti Atiyah; Elvi Sepriani (STIKES Columbia Asia Medan, 2023)
Prenatal class is a group learning facility about health for pregnant women in a face-to-face form which aims to increase the knowledge and skills of pregnant women regarding pregnancy, childbirth, postpartum, and this includes caring for newborns and exclusive breastfeeding. Participating in prenatal class activities is highly recommended for pregnant women, and then proceed to antenatal classes and breastfeeding learning classes. During pregnancy, every pregnant woman experiences various discomforts caused by hormonal changes that occur in the body due to pregnancy. During pregnancy, pregnant women experience physical, psychological and hormonal changes in the body. These changes will have an impact on discomfort during pregnancy. The prevalence of discomfort during pregnancy is around 3-17%, in developed countries 10% and in developing countries 25%, in Indonesia the incidence of discomfort during pregnancy is around 28.7%. This extension activity uses leaflet media which consists of opening, implementation and closing. The results of the service show from the evaluation stage that participants play an active role in activities, can answer questions by expressing opinions. Know about prenatal classes and the activities carried out in prenatal classes and know about discomforts during pregnancy and their handling.